Fiber Fortification in Modified Muffin Products Mocaf Flour and Oatmeal - Yusuf, Muhammad Usamah; Wasiyem, Wasiyem; Eliska, Eliska (Indonesian Journal of Global Health Research, 2024)
MOCAF is a flour product that uses the principle of modifying fermented cassava cells and has a higher fiber content than wheat flour. The purpose of this study was to fortify fiber in muffin products by modifying using MOCAF flour and adding oatmeal, and organoleptic acceptable. This research method is a true experimental and Post-test only control group design. This research was conducted in 3 stages, namely the product development stage, acceptability test, and fiber content test. Fiber test results on modified muffins of 1.85 grams per 100 grams (1.85%). Based on the overall results, the acceptance test of modified muffins was acceptable in the community and the color aspect became the most desirable aspect by the panelists and fiber fortification on modified muffins was declared successful due to the increase in fiber content. Further research needs to be done in fiber fortification in muffin products, in order to further increase the fiber content in muffins significantly.